Rehabilitation research : principles and applications - Balthazar, Catherine H.; Vendrely, Ann M. (St. Louis, Mo. : Elsevier, 2022)
Rehabilitation Research: Principles and Applications, 6th Edition helps you learn to analyze and apply research to practice. It examines traditional experimental designs, as well as nonexperimental and emerging approaches, including qualitative research, single-system designs, epidemiology, and outcomes research. Ideal for students and practitioners in physical therapy, occupational therapy, and speech-language pathology, this user-friendly resource emphasizes evidence-based practice and your development as a true scientist-practitioner
Includes bibliographical references and index
Keywords: Medical rehabilitation -- Research; Rehabilitation